(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Introduction: Information and communication technologies (ICT) continue to impact the learning landscape all over the world, particularly the use of learning management system (LMS.). The study assessed the impact of Learning Management System (LMS) in pharmacy education and explored factors influencing its adoption for learning in selected Universities in Southern Nigeria. Method: The study samples consist of 66 pharmacy lecturers and 779 undergraduate pharmacy students, drawn from four universities, by employing a multistage sampling method and primary data sources. The instruments employed were two sets of questionnaires, one for each of the lecturers and students. Collected data were summarised using descriptive statistics including frequencies, percentages, weighted averages (WA) and medians while inferential statistics namely independent samples t-tests and analysis of variance (ANOVA) were employed in answering research questions about variables at 5% level of significance. Results: The results show that the impacts of LMS in pharmacy education include improving educational outcome, for lecturers (80.8%; WA 2.7) and for students (55.5%; WA 2.2); promoting collaborative learning, for lecturers (76.9%; WA = 2.7), and among students (59.2%, WA 2.4) and promoting students’ independent learning, for lecturers (92.3%; WA 3.0) and for students (68.3%; WA 2.6)). Factors reported as important in adoption of LMS technology are institutional support for technology tools (84.9%, WA = 3.7), electricity availability (93.9%, WA = 3.8), price of technology (62.1%; WA = 3.4) and internet access (87.9%, WA=3.7). Conclusion: The study concludes that the impact of LMS technology in pharmacy education include promoting student’s independent learning, improving educational outcomes and promotion of collaborative learning among students; while the most important factors facilitating the adoption of technology for learning were electricity, availability of internet connectivity and institutional support for technology use.